BUB3, beyond the Simple Role of Partner - Patrícia M. A. Silva; Hassan Bousbaa (MDPI AG, 2022)
The BUB3 protein plays a key role in the activation of the spindle assembly checkpoint (SAC), a ubiquitous surveillance mechanism that ensures the fidelity of chromosome segregation in mitosis and, consequently, prevents chromosome mis-segregation and aneuploidy. Besides its role in SAC signaling, BUB3 regulates chromosome attachment to the spindle microtubules. It is also involved in telomere replication and maintenance. Deficiency of the BUB3 gene has been closely linked to premature aging. Upregulation of the BUB3 gene has been found in a variety of human cancers and is associated with poor prognoses. Here, we review the structure and functions of BUB3 in mitosis, its expression in cancer and association with survival prognoses, and its potential as an anticancer target.